PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK IPHONE DI KOTA SEMARANG - Oktaviona Ayuningsih, Maria; Prasetyo Widyaningtyas, Dian (Penerbit Lafadz Jaya, 2025)
The motivation behind this study is the advancement of smartphone technology in Indonesia, which has led to increased competition between brands. Despite this, the iPhone has not become a market leader, holding only the third position after Samsung and Oppo. This research aims to analyze the influence of product quality, brand image, and price on purchasing decisions for iPhone smartphones in Semarang City, both partially and simultaneously. The approach used in this study is quantitative. A total of 108 respondents were selected as the research sample. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis testing, and the calculation of the coefficient of determination (R²), all of which were processed using SPSS software version 25.0. The results of the data analysis show that in the partial test (t-test), product quality, brand image, and price have a positive and significant effect on purchasing decisions. The results of the simultaneous test (F-test) show that the F value (20.969) is greater than the F table value (2.69), with a significance value of 0.000, which is less than 0.05. It can be concluded that product quality, brand image, and price simultaneously have a positive and significant effect on purchasing decisions.